Potencial de geração, valoração comercial e proposição de um modelo de gestão de materiais recicláveis na região Oeste do Paraná - Ansilago, Mônica (2017)
The growing urbanization process and the technological advance lead to an increase in the generation of various types of waste, including recyclable waste, which despite their potential for use, end up having, for the most part, an inadequate final destination. This study aimed to identify the potential generation, commercial valuation and proposition of a management model of recyclable materials for the 50 municipalities of the western region of Paraná. The methodology included the characterization of generating sources, the qualification and quantification of the potential for the generation of recyclables, economic valuation, technological prospection and the proposal of a management model for recyclable materials. The results show the evolution of the last ten years in terms of the generate of recyclable waste. Thus, in the western region of Paraná, the total generated of canned type residues was 57.22 t day -1, styrene 12.92 t day -1, PET 18.46 t day -1, polymers 22.16 t day -1, paperboard 16.61 t day -1, carton packaging 14.77 t day -1 e glass 42.46 t day -1. In the case of the commercial valuation of recyclables in the municipalities studied, Santa Terezinha do Itaipu had the highest commercial valuation potential, with values of R$ 1.00/kg Pet, R$ 0.50/kg PVC and R$ 0.42/Kg of White Paper, being these values higher than those compared with the other municipalities. The proposal of the management model was based on intermunicipal consortia, distributed in three management regions, with anchored municipalities in Guaíra, Cascavel and Foz do Iguaçu, proposed for the implantation of a center for sorting and processing of recyclable waste. Management of region 1 would be responsible for processing 60.82 t day -1 (1,824.74 t month -1 or 22.201.03 t year -1) of recyclable waste. The management center of region 2 would be responsible for processing 57.71 t day -1 (1,731.26 t month -1 or 21,063.61 t year -1) of recyclable waste. The management center of region 3 would be responsible for processing 66.05 t day -1 (1,981.51 t month -1 or 24,108.47 t year -1) of recyclable waste. After implantation, the proposed model would allow a greater use of recyclable waste, being transformed into raw material, reinserted in the productive chain, generating employment, income and reducing negative impacts to the environment.